Garfield feeds the kitty - Davis, Jim, 1945 July 28- (New York : Ballantine, 1999)
A collection of black-and-white cartoon strips featuring Garfield the big-eating, wise-cracking, lazy cat.
"His 35th book"--Cover.
3.5
3-6
Keywords: Garfield (Fictitious character) -- Comic books, strips, etc. -- Juvenile fiction; Cats -- Comic books, strips, etc. -- Juvenile fiction; Human-animal relationships -- Comic books, strips, etc. -- Juvenile fiction; Garfield (Fictitious character) -- Fiction; Cats -- Fiction; Human-animal relationships -- Fiction; Humorous stories; Cartoons and comics; Garfield (Fictional character) -- Fiction; Cats -- Fiction; Humorous fiction; Comic books, strips, etc; Humorous fiction; Comic books, strips, etc